Profitabilitas, Solvabilitas dan Audit Delay Pada Perusahaan Consumer Goods Yang Terdaftar Di BEI - Bahtiar Effendi (Politeknik Ganesha Medan, 2018)
This study aims to examine the effect of profitability and solvency on audit delay on consumer goods companies listing on Indonesia Stock Exchange (IDX) in 2011-2016. The population of this research is all consumer goods companies in Indonesia in 2011-2016. The number of samples of 30 consumer goods companies, selected using purposive sampling method. This study uses data collected from Indonesian Stock Exchange (IDX) in 2011-2016 and also from each company web. By using multiple regression analysis as research method and result of this research revealed that found significant positive influence between solvency to audit delay and found also result that profitability have no effect to audit delay. Keywords: Profitability, Solvency, Audit Delay.